Passive infusion of an S2-Stem broadly neutralizing antibody protects against SARS-CoV-2 infection and lower airway inflammation in rhesus macaques. - Christopher T Edwards; Kirti A Karunakaran; Elijah Garcia; Nathan Beutler; Matthew Gagne; Nadia Golden; Hadj Aoued; Kathryn L Pellegrini; Matthew R Burnett; Christopher Cole Honeycutt; Stacey A Lapp; Thang Ton; et al. (PLoS Pathogens)
The continued evolution of SARS-CoV-2 variants capable of subverting vaccine and infection-induced immunity suggests the advantage of a broadly protective vaccine against betacoronaviruses (β-CoVs). Recent studies have isolated monoclonal antibodies (mAbs) from SARS-CoV-2 recovered-vaccinated donors capable of neutralizing many variants of SARS-CoV-2 and other β-CoVs. Many of these mAbs target the conserved S2 stem region of the SARS-CoV-2 spike protein, rather than the receptor binding domain contained within S1 primarily targeted by current SARS-CoV-2 vaccines. One of these S2-directed mAbs, CC40.8, has demonstrated protective efficacy in small animal models against SARS-CoV-2 challenge. As the next step in the pre-clinical testing of S2-directed antibodies as a strategy to protect from SARS-CoV-2 infection, we evaluated the in vivo efficacy of CC40.8 in a clinically relevant non-human primate model by conducting passive antibody transfer to rhesus macaques (RM) followed by SARS-CoV-2 challenge. CC40.8 mAb was intravenously infused at 10mg/kg, 1mg/kg, or 0.1 mg/kg into groups (n = 6) of RM, alongside one group that received a control antibody (PGT121). Viral loads in the lower airway were significantly reduced in animals receiving higher doses of CC40.8. We observed a significant reduction in inflammatory cytokines and macrophages within the lower airway of animals infused with 10mg/kg and 1mg/kg doses of CC40.8. Viral genome sequencing demonstrated a lack of escape mutations in the CC40.8 epitope. Collectively, these data demonstrate the protective efficiency of broadly neutralizing S2-targeting antibodies against SARS-CoV-2 infection within the lower airway while providing critical preclinical work necessary for the development of pan-β-CoV vaccines.